2007
DOI: 10.1007/s00449-007-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Response surface method to optimize the production and characterization of lipase from Penicillium verrucosum in solid-state fermentation

Abstract: Current studies about lipase production by solid-state fermentation involve the use of agro-industrial residues towards developing cost-effective systems directed to large-scale commercialization of enzyme-catalyzed processes. In this work, lipase production and partial characterization of the crude enzymatic extracts obtained by Penicillium verrucosum using soybean bran as substrate was investigated. Different inductors were evaluated and the results showed that there is no influence of this variable on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 27 publications
6
56
1
4
Order By: Relevance
“…Sekhon et al,(2006) has reported on the use of malt extract as a source of nitrogen for lipase production. There exist reports on the use of soy meal as a source of nitrogen but more reported that it was found not to be the best source with any organism (Essakkiraj et al, 2010;Vargas et al, 2008;Kempka et al, 2008). This could mean that soymeal contain certain cations which repress or inhibit lipase activity and can only be employed when these cations had been removed by an ionexchanger; which when considered from the economic standpoint may not be ideal or good for lipase production or may be costintensive.…”
Section: Resultsmentioning
confidence: 99%
“…Sekhon et al,(2006) has reported on the use of malt extract as a source of nitrogen for lipase production. There exist reports on the use of soy meal as a source of nitrogen but more reported that it was found not to be the best source with any organism (Essakkiraj et al, 2010;Vargas et al, 2008;Kempka et al, 2008). This could mean that soymeal contain certain cations which repress or inhibit lipase activity and can only be employed when these cations had been removed by an ionexchanger; which when considered from the economic standpoint may not be ideal or good for lipase production or may be costintensive.…”
Section: Resultsmentioning
confidence: 99%
“…These are enzymes belonging to the group of hydrolases that present as main biological function to catalyze the hydrolysis of insoluble triacylglycerols to generate free fatty acids, mono and diacylglycerols and glycerol (20,26). Ester synthesis is carried out in aqueous media in the presence of various lipases (23).…”
Section: Introductionmentioning
confidence: 99%
“…A produção de lipases foi realizada segundo condições otimizadas de temperatura (27,5 °C) e umidade inicial do substrato (55%) (KEMPKA et al, 2008).…”
Section: Produção E Concentração De Lipasesunclassified
“…À 10 g de farelo fermentado foram adicionados 45 mL de tampão fosfato de sódio 100 mM pH 7,0 em Erlenmeyers de 250 mL, seguido de incubação a 37 °C em agitador orbital a 150 rpm durante 30 minutos. A extração da fração líquida foi realizada por prensagem manual em filtro (KEMPKA et al, 2008).…”
Section: Extração Das Lipases Do Farelo Fermentado E Concentraçãounclassified